CD14+CD16+ monocytes are involved in daratumumab‐mediated myeloma cells killing and in anti‐CD47 therapeutic strategy. (12th March 2020) - Storti, Paola; Vescovini, Rosanna; Costa, Federica; Marchica, Valentina; Toscani, Denise; Dalla Palma, Benedetta; Craviotto, Luisa; Malavasi, Fabio; Giuliani, Nicola
Summary: A deep elucidation of the mechanisms of action of anti‐CD38 monoclonal antibodies (mAbs), such as daratumumab (DARA), is required to identify patients with multiple myeloma (MM) who are more responsive to this treatment. In the present study, an autologous ex vivo approach was established, focussing on the role of the monocytes in the anti CD38‐mediated killing of MM cells. In bone marrow (BM) samples from 29 patients with MM, we found that the ratio between monocytes (CD14 + ) and MM cells (CD138 + ) influences the response to DARA. Further, the exposure of the BM samples to DARA is followed by the formation of a CD138 + CD14 + double‐positive (DP) population, that quantitatively correlates with the anti‐MM cells killing. These effects were dependent on the presence of a CD14 + CD16 + monocyte subset and on high CD16 expression levels. Lastly, the addition of a mAb neutralising the CD47/signal‐regulatory protein α (SIRPα) axis was able to increase the killing mediated by DARA. The effects were observed only in coincidence with high CD14 + :CD138 + ratio, with a significant presence of the DP population and were correlated with CD16 expression. In conclusion, the present study underlines the critical role of the CD16 + monocytes in DARA anti‐MM killing effects and gives a rationale to test the combination of an anti‐CD47 mAb with anti‐CD38 mAbs.